Sex differences in risk factors for Alzheimer dementia encephalopathy patients - O’Brien, Connor John; Patterson, James Wayne; Ojo, Dami Taiwo; Faulstich, Nathan Gerhard; Bucci, Killian Joseph; Brewer, Philip Cole; Imeh-Nathaniel, Adebobola; Nathaniel, Emmanuel I.; Roley, Laurie; Goodwin, Richard; Nathaniel, Thomas I. (Frontiers in Dementia, 2025)
BackgroundThe objective is to identify risk factors that contribute to sex differences in Alzheimer dementia (AD) patients with encephalopathy (ADEN) and determine whether these factors are different between male and female ADEN patients. This is the first large-scale study comparing sex-specific ADEN risk profiles.MethodsOur retrospective cohort study analyzed data collected from February 2016 to August 2020. It included a total of 128,769 AD patients, among whom 41,266 AD patients also presented with encephalopathy, compared to 87,503 AD patients that did not. The univariate analysis was used to determine differences in risk factors for male and female AD patients. Multivariate analysis predicted specific risk factors associated with male and female ADEN patients.ResultIn the adjusted analysis, males presented with hypertension (OR = 1.144, 95% CI, 1.094–1.197, p < 0.001), peripheral vascular disease (OR = 1.606, 95% CI, 1.485–1.737, p < 0.001), atrial fibrillation (OR = 1.555, 95% CI, 1.443–1.676, p < 0.001), hallucinations (OR = 1.406, 95% CI, 1.119–1.766, p = 0.003), and traumatic head injury (OR = 3.211, 95% CI, 2.346–4.395, p < 0.001). Females presented with osteoporosis (OR = 0.307, 95% CI, 0.278–0.340, p < 0.001), unspecified cancer (OR = 0.615, 95% CI, 0.512–0.740, p < 0.001), anxiety (OR = 0.609, 95% CI, 0.565–0.655, p < 0.001), urinary tract infections (UTI) (OR = 0.451, 95% CI, 0.423–0.481, p < 0.001), upper respiratory infections (URI) (OR = 0.531, 95% CI, 0.432–0.653, p < 0.001) and gastrointestinal ulceration (OR = 0.338, 95% CI, 0.269–0.424, p < 0.001).ConclusionOur analysis identified risk factors that contribute to sex differences in ADEN. This difference was fully mediated by peripheral vascular disease, atrial fibrillation, hallucinations, and traumatic head injury for males and unspecified cancer, anxiety, urinary tract infections, upper respiratory infections, and gastrointestinal ulceration for females. These findings provide valuable insights into the risk factors that can be managed to improve the care of male and female ADEN patients.